Moscow internal medicine school: Dmitry Dmitrievich Pletnev and Miron Semenovich Vovsi - E. Yu. Ebzeeva (Кардиоваскулярная терапия и профилактика)
The article presents a brief overview of the history of the development of internal medicine schools in Russia. The role of internal medicine researches Matvey Yakovlevich Mudrov and Grigory Antonovich Zakharyin in their creation is noted. The key moments of the biography of Miron Semenovich Vovsi, the founder of the Soviet internal medicine school, who made a huge contribution to the creation of the national nephrology school, are reflected. The role of M. S. Vovsi as a clinician and organizer of military field therapy is consecrated. Due to the fact that D. D. Pletnev and the Moscow scientific school had a decisive influence on the formation of M. S. Vovsi as a scientist and clinician. The article presents biographical information about D. D. Pletnev and his creative path. The issues of clinical medicine, the study of which was devoted to the scientific and professional activities of D. D. Pletnev, are consecrated. The article also provides data about the followers of M. S. Vovsi, his students, who continued the best traditions of the internal medicine school of the great teacher.